Antibacterial Diterpenoid Against Pathogenic Oral Bacteria of Streptococcus Mutans ATCC 25175 Isolated From Sarang Semut (Myrmecodia Pendans) - Mieke H Satari; Boima Situmeang; Indah Permata Yudha; Dikdik Kurnia (Syarif Hidayatullah State Islamic University, 2019)
Discovery of new antibacterial agent to treat oral disease caused by pathogenic oral bacteria is an attracted focus to more pay attention of researcher. The tropical natural product is the promising sources of new bioactive as antibacterial compounds. The epiphyte plant of Sarang Semut (M. pendans) empirically has been used as a drug to treat various diseases. Our previous research found that ethyl acetate extract of Sarang Semut inhibited the bacteria growth of Enterococcus faecalis. This study aims to isolate, structure determination and antibacterial activity evaluation of active compound against Streptococcus mutans ATCC 25175. The isolation by combination chromatography on normal and reverse phase resulted an antibacterial compound 1. Based on the analysis of the spectroscopic data including IR, FTIR, 1H-NMR, 13C-NMR, 2D-NMR as well as by mass spectroscopic (MS) and compare to reported data, structure of compound 1 was suggested as terpenoid type diterpene derivative. Antibacterial activity evaluation by Kirby-Bauer method of compound 1 against S. mutans ATCC 25175 showed inhibition zone values were 17.8, 14.5 and 11.1 mm at 10000, 5000 and 1000 ppm, respectively, while the MIC and MBC values were 18.125 ppm with MBC of 2500 ppm, respectively.